Un ejemplo de rentabilidad comunicativa en la sintaxis del español: los grupos complementarios - Jiménez Juliá, Tomás (Studia Romanica Posnaniensia, 2019)
Coordination has been described far more rigidly than its actual usage shows. This paper describes cases of coordination structures in Spanish that break with some commonly held ideas and show that the search for communicative efficiency in languages rises above rigid formal rules